Media bias : finding it, fixing it - Sloan, W. David (William David), 1947-; Mackay, Jenn Burleson, 1975- (Jefferson, N.C. : McFarland & Co., 2007)
"Scholars examine prevailing arguments about media bias from a non-polemical perspective, including ideology, politics, television, photography, religion, abortion, homosexuality, gender, race, crime, environment, region, military, corporate ownership, labor and health. Each essay introduces the topic, argues for or against, assesses the evidence for all arguments, and includes a list of suggested readings"--Provided by publisher.
Introduction: the bias debate / Wm. David Sloan -- Reporting the Israeli-Palestinian conflict: a personal view / Bruce J. Evensen -- Ideology / Michael Ray Smith -- Political partisanship / Debra Reddin van Tuyll and Hubert P. van Tuyll -- Religion / Katie H. Porterfield -- Abortion / Stephen E. Stewart -- Homosexuality / Dave Cassady -- Gender / Ginger Miller Loggins -- Race and ethnicity / Tamara K. Baldwin and Henry M. Sessons -- Crime / Kay Best Murphy -- The environment / Kim Cross -- Regional bias / Randall S. Sumpter -- The military / Christina Jesson -- Television news / Jenn Burleson Mackay -- Photojournalism / Patrick Beeson -- Corporate ownership / Katharine A. Birchall -- Management and labor / Karen Watts Perkins -- Health and medicine / Carmen S. Brown.
Includes bibliographical references and index.
Keywords: Journalism -- Objectivity -- United States